A tool for pilot’s performance and engagement assessment in helicopter flight simulator - Kopyt, A.; Tomaszewska, P. (My University, 2019)
The accurate training procedures for future pilots are essential. There is need for objective performance and engagement assessment method. Only the combination of these two factors gives a full picture of pilot’s behaviour during the flight. This is the idea behind the general Objective Assessment Tool (gOAT) system. In the paper we present a tool for pilot’s performance assessment and the obtained results. One of the main advantages of the proposed method is high resolution enabling detailed, quantitative comparison of different flights. The solution combines many diverse criteria (varying largely in the range of obtained values) in order to generate one, scalar, easy comparable mark. The presented method was evaluated on data collected in helicopter flight simulator while performing the slalom Mission Task Element (MTE) adopted from ADS 33 [7]. The results analysis confirmed that the algorithm can accurately distinguish between the best and worst flights in terms of their handling quality, also appropriately points flights with similar performance. Thus it opened a path to create a fully objective system for detailed training assessment and pilot’s progress analysis. The advantage of the system is that its applications are not only limited to helicopter flight simulators. It could be also used in UAVs or mobile robots.